High-cycle fatigue constitutive model and a load-advance strategy for the analysis of unidirectional fiber reinforced composites subjected to longitudinal loads. (15th July 2019) - Barbu, Lucia G.; Oller, Sergio; Martinez, Xavier; Barbat, Alex H.
Abstract: A fatigue constitutive model valid for the composite constituent will be presented in this paper. The composite behaviour will be obtained by means of the serial/parallel mixing theory that is also used as a constitutive equation manager. The constitutive formulation is coupled with a load advancing strategy in order to reduce the computational cost of the numerical simulations. Validation of the constitutive formulation is done on pultruded glass fiber reinforced polymer profiles. Special emphasis is made on the comparison between the experimental and the numerical failure mode.